Does ESG Reporting Relate to Corporate Financial Performance in the Context of the Energy Sector Transformation? Evidence from Poland - Michał Baran; Aneta Kuźniarska; Zbigniew J. Makieła; Anna Sławik; Magdalena M. Stuss (Energies, 2022)
This paper aims to investigate whether the environmental, social and corporate governance (ESG) score of companies operating in the energy sector is associated with their corporate financial performance (CFP). The research covered data from eight companies with a dominant position in the Polish energy sector. The research used the comparative analysis between ESG performance and accounting-based measures of profitability: return on equity (ROE), return on assets (ROA) and return on sales (ROS). Additionally, reference was also made to the DuPont model. The acquired results do not reveal repetitive dependencies that would facilitate the discovery of a pattern of the impact of the factors of ESG on the financial performance of enterprises. Despite indicating the cases of correlations between the ESG scores and CFP at a high level, indeed sometimes at a very high level, the particular case studies significantly differ from each other. This may be caused by the fact that Polish enterprises from the energy sector illustrate far-reaching specifics, among others, with regard to the key significance of the entities with a prevalent state ownership and strict administrative regulations, which are subject to the energy market, state of development and structure of the whole sector in Poland. Thus, this is also why the mechanisms or dependencies, whose existence it is possible to expect in conditions of free competition, may be weakened or even eliminated in Polish conditions.